2002
DOI: 10.1021/es025638k
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mobilization of Colloids and Transport of Cesium in Hanford Sediments

Abstract: Radioactive waste, accumulated during Pu production, has leaked into the subsurface from underground storage tanks at the U.S. Department of Energy's Hanford site. The leaking solutions contained 137Cs and were of high ionic strength. Such a tank leak was simulated experimentally in steady-state flow experiments with packed Hanford sediments. The initial leak was simulated by a 1 M NaNO3 solution, followed by a decrease of ionic strength to 1 mM NaNO3. Cesium breakthrough curves were determined in both 1 M and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 21 publications
2
85
0
Order By: Relevance
“…The experimental evidence also suggests that, upon disturbances of ionic strength, in situ colloid mobilization may be an important transport mechanism for contaminant species [31]. If the disturbance of ionic strength occurs in combination with the presence of sorbing contaminants, the mobilized particles may also likely act as vectors for accelerated contaminant movement [41]. Saiers and Hornberger [31] also experimentally found that under conditions of low pore water ionic strength, the kaolinite colloids significantly accelerate 137 Cs transport through column packed with quartz sand.…”
Section: Chemically Induced Release Processesmentioning
confidence: 97%
See 2 more Smart Citations
“…The experimental evidence also suggests that, upon disturbances of ionic strength, in situ colloid mobilization may be an important transport mechanism for contaminant species [31]. If the disturbance of ionic strength occurs in combination with the presence of sorbing contaminants, the mobilized particles may also likely act as vectors for accelerated contaminant movement [41]. Saiers and Hornberger [31] also experimentally found that under conditions of low pore water ionic strength, the kaolinite colloids significantly accelerate 137 Cs transport through column packed with quartz sand.…”
Section: Chemically Induced Release Processesmentioning
confidence: 97%
“…A comprehensive amount of literature exists on the topic of colloid mobilization and transport in model and natural systems [7,10,14,22,24,27,41,87,88]. Considerable advances have been made on the prediction of colloidal transport using experimental laboratory and field studies as well as numerical models [87,89,90].…”
Section: Stability Of Dispersed Colloidal Particles and Their Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…These contaminant-attached soil particles may themselves become mobile and move through the soil and eventually reach the water bodies (fig 2). This is commonly known as colloid-facilitated contaminant transport [9,11,14,16,20,23,41,52,56]. Colloids are a ubiquitous component of subsurface systems and play an important role in radioactive contaminant fate and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent colloid transport might have contributed to the deep migration of contaminants (7,8). Under the DOE's initiative on cleanup of the Hanford Site, recent studies have resulted in a variety of findings relevant to contaminant transport, including identifying the mechanisms for sorption of Cs + in sediments (9,10), the formation of cancrinite as a secondary mineral phase (11,12), the geochemical evolution of waste plumes (13,14), the effect of cation exchange on Cs + sorption (15,16), and the effect of colloids on Cs + transport (17).…”
Section: Introductionmentioning
confidence: 99%